Multilingualism in Hong Kong: A Social Identity Theory Perspective - Chan, Pak Hei (Trinity College Dublin. School of Linguistic Speech & Comm Sci. C.L.C.S., 2023)
The linguistic situation in Hong Kong is often described as being trilingual and biliterate. This thesis sets out to examine the link between language and the sense of national identity in Hong Kong from a social identity perspective. It aims to find out whether language use, proficiency and attitudes are linked to one's perceived identity in contemporary Hong Kong, in the context of the city's context of trilingualism (Cantonese, English, Mandarin) and biliteracy (Chinese and English). The study adopts a mixed-method approach and involves three research instruments: an online questionnaire, a verbal-guise test, and a semi-structured interview. A total of 113 participants completed the online questionnaire, and six completed the verbal-guise test and the semi-structured interview. The data is analysed through the lens of social identity theory set out by Tajfel (1972)
APPROVED
Keywords: English; Multilingualism; Hong Kong; Social Identity Theory; Language; Identity; Language Use; Language Proficiency; Language Attitudes; Cantonese; Mandarin